A study on connotative equivalence between Gone with the wind" and its translation in Vietnamese by Duong Tuong . M.A Thesis Linguistics: 60 22 1 - Nguyễn, Thị Diệu Thúy (University of Languages and International Studies, 2017)
The researcher conducted a study to investigate the kinds of connotative equivalence between the novel Gone with the wind" and its translated version by Duong Tuong. Different kinds of connotative equivalence have been identified. Technical data from both (...)"